Effect of temperature on kinetics of bulk polymerization of methyl acrylate - Fatin Azureen, Zulkurnain (2014)
This research objective is to determine the effect of temperature on the kinetics of bulk polymerization of methyl acrylate. Because of previous research has mentioned that free radical polymerization is poorly controlled and results in high molecular weight, this research will be run at certain temperature which can be considered high but it should be lower than the boiling point of the monomer itself. The method used in this research is by using Differential Scanning Calorimetry (DSC). The DSC will measure the heat flow associated with polymerization as a function of time in a controlled atmosphere. Therefore, the change in the kinetics of polymerization based on temperature can be determined by using this equipment. The graph for heat flow versus time is recorded by DSC software until the reaction is completed. By referring to the graph it can be seen that the reaction rate of polymerization increase with the increase of temperature. As a conclusion, from this research, it can be seen that changing the temperature can affect polymerization kinetics of methyl acrylate